Writing Skill Development through the Assignment of Retelling Important Events - Sukristanto, Sukristanto (EDUCARE, 2009)
ABSTRACT: This study was aimed at improving the writing skill through the assignment of retelling recorded important events on the 5th grade of SDN (Sekolah Dasar Negeri or Elementary School) 2 Pabuwaran in Banyumas, Central Java, Indonesia. As a classroom action research, it was done in three cycles. Each cycle consisted of three meetings. Each cycle consisted of (1) planning, (2) action, (3) observation and evaluation, and (4) reflection. The plan of each phase was based on the changes, which were known in accordance with the observed factors, namely students, teacher, and learning activity. Subjects of this study were 27 students. The analysis and test result showed that (1) there was a raising level of students activity i.e. the progressive increase of studentsâ participation on writing subject; (2) there was studentsâ sensitivity increase upon their surrounding either at school or home; (3) there was an increase on teacher activity during the learning process; and (4) as a consequence, the studentsâ writing skill through retelling the important event also increased. The cycle-test results showed that the mean of writing skill were as follows: 58.9 in cycle I, 67.5 in cycle II, and 79 in cycle III.KEY WORDS: writing, retelling important events, practice, three cycles, and classroom action research.Â Â About the Author: Drs. Sukristanto, M.Hum. is a Senior Lecturer at the Department of Indonesia and Local Language Education, Faculty of Education UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, PO Box 202, Purwokerto 53182, Central Java, Indonesia. He can be reached at: sukristanto@yahoo.co.idÂ Â How to cite this article? Sukristanto. (2009). âWriting Skill Development through the Assignment of Retelling Important Eventsâ in EDUCARE: International Journal for Educational Studies, Vol.2(1) August, pp.47-54. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 14, 2009); Revised (July 14, 2009); and Published (August 17, 2009).